The upper gastrointestinal endoscopic and rectosigmoidoscopic findings in Behçet's disease - M. Kadir AKSÖZ; Belkıs ÜNSAL; İlgül ZEREN; G. ÖNDER; N. EKİNCİ; Sadun KOŞAY (Turkish Journal of Gastroenterology, 2020)
-